Processo de medição de desempenho em micro e pequenas empresas de um arranjo produtivo local - Oliveira, Karla Fabricia de; Vieira, Ariana Martins; Cavenaghi, Vagner; Galdamez, Edwin Vladimir Cardoza [UNESP] (My University, 2010)
The local productive arrangements (LPA) are organizational mechanisms that enable the continuous performance of small businesses in production processes and business management models. To promote continuous improvement is essential that companies make decisions based on data that reflects business’ performance (performance measurement) and promote the cluster performance. This way, the aim of this article is to describe the performance measurement process that will support the corporate management of Micro and Small enterprises (SME) of a Local Productive Arrangement in Maringá, State of Paraná, Brazil. To develop this paper, the bibliographic search and action research methods were used. The field research was developed from the cooperation project (PROJVEST) conducted at the LPA, which goal is to deploy improvement actions in project’s participating companies. Metrics and performance indicators constructed from the diagnosis in the areas of Production, Quality and Ergonomics in companies will be presented. Among the main results, can be pointed out that the performance management of LPA is promoting the introduction of corporate management practices in SMEs, stimulating business cooperation, the continuous innovation in manufacturing processes and product quality and business processes.

Os Arranjos Produtivos Locais (APLs) são mecanismos organizacionais que viabilizam o desempenho contínuo das empresas de pequeno porte nos processos de produção e nos modelos de gestão empresarial. Para promover a melhoria contínua é fundamental que as empresas tomem decisões baseados em dados que reflitam o desempenho empresarial (Medição de Desempenho) e promova o desempenho do aglomerado. Desta forma, o objetivo deste artigo é descrever o processo de medição de desempenho que dará suporte a gestão empresarial das Micro e Pequenas Empresas (MPEs) de um Arranjo Produtivo Local de Maringá do Estado do Paraná, Brasil. Para desenvolver o trabalho o método foi a pesquisa bibliográfica e pesquisa-ação. A pesquisa de campo foi desenvolvida a partir do projeto de cooperação (PROJVEST) conduzido no APL, cujo objetivo é implantar ações de melhoria nas empresas participantes do projeto. Serão apresentadas métricas e indicadores de desempenho construídos a partir do diagnóstico nas áreas de Produção, Qualidade e Ergonomia nas empresas. Entre os principais resultados podem se destacar que a gestão de desempenho do APL está promovendo a introdução de práticas de gestão empresarial nas MPEs, estimulando a cooperação empresarial, a inovação contínua nos processos de manufatura e qualidade dos produtos e processos das empresas. Palavras-chave: Medição de Desempenho; Indicadores de Desempenho; Arranjo Produtivo Local; Micro e Pequenas Empresas.
Performance measurement process in smes of a local productive arrangement (LPA)
Keywords: Performance measurement; Performance indicators; Local productive arrangement; Small and medium enterprises (SMEs); Medição de desempenho; Indicadores de desempenho; Arranjo produtivo local; Micro e pequenas empresas